(untitled) - Jang, Michael (Indianapolis, IN, 2006)
Mastering Fedora Core 5 contains more than a thousand pages of in-depth coverage, including new installation procedures, the very latest utilities, and high-level discussions of new commands and applications. Here's the practical information you need to install, configure, and administer the latest version of Fedora as a network or a desktop operating system.
Keywords: Operating systems (Computers),Hệ điều hành (máy tính)